2001
DOI: 10.1093/emboj/20.11.2655
|View full text |Cite
|
Sign up to set email alerts
|

C26-CoA-dependent ceramide synthesis of Saccharomyces cerevisiae is operated by Lag1p and Lac1p

Abstract: Lag1p and Lac1p are two highly homologous membrane proteins of the endoplasmic reticulum (ER). When both genes are deleted, cells cannot transport glycosylphosphatidylinositol (GPI)-anchored proteins from the ER to the Golgi at a normal rate. Here we show that microsomes or detergent extracts from lag1D lac1D double mutants lack an activity transferring C26 fatty acids from C26-coenzyme A onto dihydrosphingosine or phytosphingosine. As a consequence, in intact cells, the normal ceramides and inositolphosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
252
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(263 citation statements)
references
References 50 publications
10
252
0
1
Order By: Relevance
“…An in vitro enzyme activity for CoA-dependent (dihydro)ceramide synthase was measured using microsomal preparations of UM-SCC-22A cells for the incorporation of stearoyl-or palmitoyl CoA into [ 3 H]dihydro-sphingosine for the generation of C 18 -or C 16 -ceramides, respectively, as described previously (17).…”
Section: In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…An in vitro enzyme activity for CoA-dependent (dihydro)ceramide synthase was measured using microsomal preparations of UM-SCC-22A cells for the incorporation of stearoyl-or palmitoyl CoA into [ 3 H]dihydro-sphingosine for the generation of C 18 -or C 16 -ceramides, respectively, as described previously (17).…”
Section: In Vitromentioning
confidence: 99%
“…Bars, SD. The generation of (B) 17C 18:1 -, 17C 14 -, 17C 18 -, and 17C 20 -ceramides or (C) 17C 16 -, 17C 24 -, and 17C 24:1 -ceramides or 17C-sphingosine in response to gemcitabine, doxorubicin, or gemcitabine/doxorubicin in these cells were also measured by LC/MS. The results are representative of at least two independent experiments; bars, SD.…”
Section: In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Both lag‐ 1 and lac‐1 have been demonstrated to play important roles in ceramide synthesis in yeast, acting as components of ceramide synthases responsible for converting dihydrosphingosine or phytosphingosine into ceramides (Guillas et al., 2001). From our recent publication, we found that a lag‐1 knockout combined with a band ( bd) mutation in N. crassa (more recently identified with the mammalian protooncogene ras‐1, Belden et al., 2007) seemed to halt the proper functioning of the clock, as revealed by race tube experiments and 48 hour expression profiling of the frq clock oscillator (Case et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The initial steps resulting in ceramide synthesis occur in the endoplasmic reticulum. A pair of homologous genes, LAG1 and LAC1, has been identified in the budding yeast Saccharomyces cerevisiae and is required for this step 2,3 . After trans-∆4-unsaturation of the sphingoid chain by the DES1 desaturase 4 , conversion of ceramide into sphingomyelin, the next enzymatic step, occurs in the Golgi compartment.…”
mentioning
confidence: 99%